DOES FINANCIAL LITERACY AMPLIFY DIGITAL BANKING'S IMPACT ON STUDENT SAVING BEHAVIOR? - Aprillia Afenny; Shandy Puspita (EP FEB UNS, 2026)
Digital banking adoption among college students is growing rapidly, but this is not necessarily accompanied by an increase in planned savings behavior. This study aims to fill this gap by examining how usage intensity, perceived ease of use, and feature utilization of the blu by BCA app collectively shape student savings behavior. It also examines the role of financial literacy as both a direct and moderating factor, a combination that has not been widely studied in the context of neobanks in Indonesia. The study employed a quantitative approach with an explanatory survey design among 200 active college students in West Jakarta who had used the blu by BCA app for at least three months. Data were collected through an online Likert-scale questionnaire and analyzed using PLS-SEM with the assistance of SmartPLS 4. All seven hypotheses were supported. Feature utilization was the strongest predictor of savings behavior, followed by usage intensity and perceived ease of use. Financial literacy was shown to have a direct and strengthening effect on all three pathways, although the moderating effect was weak to moderate. The overall model explained 61.5% of the variation in savings behavior with a high level of model fit. These findings confirm that feature design oriented towards financial goals, rather than simply ease of transactions, is a key driver of planned savings behavior. From a policy perspective, integrating digital-based financial literacy programs into higher education curricula is relevant given their role in optimizing the benefits of banking technology. This research provides a conceptual contribution by developing a TAM model that integrates financial literacy as a moderator in the neobank ecosystem, with practical implications for app developers, regulators, and educational institutions.